Approximation of functions of two variables by polynomial spline on the basis of third-order splines - Білецький, А. Я.; Приставка, П. О. (Proceedings of National Aviation University, 2002)
The asymptotic properties of a local polynomial spline of two variables on the basis of the third-order B splines are studied. Appropriate theorems are formulated and proved. An example of payment implementation in data processing is given.